Robust Framework For Digital Image Denoising And Deblurring - Toh, Kenny Kal Vin (2012)
Image restoration concerns improving visual quality of a captured image that goes beyond the achievable limit of camera. Recent advancement in imaging and multimedia technology has advocated the interests of image restoration through software, of which applications permeate consumer photography as well as different industries. Unfortunately, the captured images often suffer from degradations, such as blurring, noise, unpleasant artifacts, and more, due to limitations of the imaging system. Despite considerable efforts have been channeled to advance the state-of-the-art methods, surprisingly, these methods are often slow and only designed for handling specific degradation model.